Ecossistemas de inovação: uma abordagem a partir da perspectiva das capacidades dinâmicas - Santini, Mateus Augusto Fassina (Universidade do Vale do Rio dos Sinos, 2023)
Studies on innovation ecosystems have been gaining ground in recent years, motivated by the economic and social gains that these environments generate, but it is still observed in the existing literature an emphasis on establishing concepts on the subject without a specific focus on the capabilities and attributes that influence development of innovation ecosystems. Considering that most innovation ecosystems in territories do not emerge spontaneously, but as a result of deliberate experimentation by different actors, the present study has the general objective of proposing a conceptual framework on the dynamic capabilities necessary for the development of innovation ecosystems in their different ways. Life stages. To respond to this objective, a comparative qualitative analysis was carried out on the five dynamic capabilities of innovation ecosystems identified in the literature: human and entrepreneurial capability, structural and financial capability, relational capability, governance capability and competitive capability. This analysis was developed at each of the four stages of innovation ecosystem development. The results suggest, among other conclusions, that the birth stage is the “orchestration stage”, since in this first stage a greater synergy between the capabilities of innovation ecosystems is essential, with the need for a greater presence of these, together, for achieving success. The growth stage is characterized by the “structural-agent” strategy, as its best results are combinations that rely on human and entrepreneurial capability and structural and financial capability. Stage III, maturity, can also be characterized by the “governance stage”, considering that the combinations that adopted strategies with this capacity presented more satisfactory results. In the last stage, renewal, the strategy that proved to be the most effective is the “relational strategy”, as the municipalities that adopted it showed better performances. Finally, this study contributes to the literature by deepening the studies on the evolution of the life stages of innovation ecosystems, as well as making the application of dynamic capabilities more comprehensive for an ecosystemic logic. From a managerial point of view, this study contributes to managers by proposing strategies to achieve success in the different stages of life of innovation ecosystems, with a focus on contexts of developing countries.
Keywords: Ecossistemas de Inovação; Capacidades dinâmicas baseadas no conhecimento; Metassíntese; QCA; Innovation ecosystems; Knowledge-based dynamic capabilities; Meta-synthesis; ACCNPQ::Ciências Sociais Aplicadas::Administração